2019
DOI: 10.1007/s10278-019-00201-7
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Catheter and Tube Detection in Pediatric X-ray Images Using a Scale-Recurrent Network and Synthetic Data

Abstract: Catheters are commonly inserted life supporting devices. X-ray images are used to assess the position of a catheter immediately after placement as serious complications can arise from malpositioned catheters. Previous computer vision approaches to detect catheters on X-ray images either relied on low-level cues that are not sufficiently robust or only capable of processing a limited number or type of catheters. With the resurgence of deep learning, supervised training approaches are begining to showing promisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In a study by Yi et al [ 52 ], the authors used data with synthetic nasogastric tubes, endotracheal tubes and umbilical catheters to test their algorithm. The precision (i.e.…”
Section: Current Landscape Of Artificial Intelligence Products In Thoracic Radiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Yi et al [ 52 ], the authors used data with synthetic nasogastric tubes, endotracheal tubes and umbilical catheters to test their algorithm. The precision (i.e.…”
Section: Current Landscape Of Artificial Intelligence Products In Thoracic Radiologymentioning
confidence: 99%
“…The precision (i.e. true positives / [true positives + false positives]) for their algorithm was 0.80 [ 52 ]. According to the authors, their work can contribute to the development of a system that detects all lines and catheters in X-ray images and could be used to prioritize images that show malpositioned lines and request urgent review by the radiologist [ 52 ].…”
Section: Current Landscape Of Artificial Intelligence Products In Thoracic Radiologymentioning
confidence: 99%
“…Another study showed AI-based computer-aided design software flagged fewer false-positives per image in digital mammograms than FDA-approved computeraided design software, with no reduction in sensitivity [4]. And there have been noteworthy developments for AI in other areas too, such as the treatment planning of brain tumors and the identification of catheters and tubes in pediatric x-ray images [5,6].…”
Section: Progress In the Application Of Ai In Medical Imagingmentioning
confidence: 99%
“…Yi et al proposed a way to generate synthesized catheters on pediatric radiographs and used synthetic data to train a segmentation network for commonly seen catheters including endotracheal tubes, nasogastric tubes, and umbilical catheters. 33 A similar approach has been explored for the detection of endotracheal tubes on adult chest radiographs, achieving an AUROC of 0.99 in classifying the presence of endotracheal tubes. 34 A more in-depth review of the current status of AI for catheter placement assessment can be found in the study by Yi et al 35 In 2019, IBM and MICCAI cohosted the Multimodal Learning for Clinical Decision Support Challenge that was dedicated to catheter detection and classification.…”
Section: Assessment Of Lines and Tubesmentioning
confidence: 99%